An optimization-based cooperative game approach for allocation of costs and benefits in interplant process integration - Tan, Raymond Girard R. (Animo Repository, 2015)
Process Integration (PI) techniques have been established as an effective means of reducing resource consumption and emissions in industrial operations. Insight-based, mathematical programming and hybrid approaches have been developed to enable integration schemes to be optimized rigorously. More recently, the use of PI tools in conjunction with Industrial Ecology (IE) concepts, particularly Industrial Symbiosis (IS), has been proven to unlock the possibility of even greater gains than from integration of process units within a single player/company site. Such integration is facilitated by the advent of Eco-Industrial Parks (EIPs) which uses geographic clustering to promote sustainable exchange of materials and energy streams among different plants and companies. On the other hand, such interplant integration is not easily dealt with using classical PI methods, since the ownership of each company by an independent entity introduces a complicating aspect to the system. Specifically, each potential partner company will participate in a symbiosis scheme specifically with the motivation of increasing its own profits. However, the self-interest of each partner company often results in a conflict of interest. If such conflict is not resolved, it may result in the failure of the symbiosis scheme. To address this problem, different approaches have been developed. One general approach based on cooperative game theory involves pooling the benefits, and then subsequently developing a rational and defensible scheme for sharing the incremental profits among the partners. Maali (2009) proposed an optimization-based cooperative game model that includes theorems in a linear programming model to solve multi-objective problems and it was proved that the solutions are always Pareto-optimal. In this work, we propose an application of Maali's method for interplant heat integration. The approach is demonstrated using a literature case study, and the results are compared with those determined via alternative cooperative game techniques. Copyright © 2015, AIDIC Servizi S.r.l.,.